FACTORS OF FORMATION OF IMAGINATION IN PRESCHOOL CHILDREN - Raxmatova Ikbolxon Inomjonovna; O’ngboyeva Maftuna Isoq qizi (Journal of new century innovations, 2022)
Annotation: In this article, the specific characteristics of the development of children's visual activities, their close connection with other educational and educational work tasks, and the reliance of the educator on the knowledge acquired in other activities of children during the training of visual activities, in-depth training of children in visual activities the teachers' preparation for painting, clay, appliqué, the ability to use pencil and paint on paper, the factors of imagination formation in preschool children are covered.